The investigation of BTLA single-nucleotide polymorphisms in patients with Behcet disease in Elazig province - Cetin, Yasin; Ilhan, Nafiye Fulya; Sen, Deniz; Celik, Sevim Karakas (Walter de Gruyter Gmbh, 2020)
Objective: Behcet Disease (BD) is a systemic chronic autoinflammatory disorder that significantly increases mortality and morbidity. Although B- and T-Iymphocyte attenuator (BTLA) is important in regulating lymphocyte activation during inflammation and infection, it is unclear whether any polymorphism in the gene encoding the BTLA is associated with autoimmune diseases and cancer. The goal of the study was to research the relationship between the alleles, genotypes and haplotypes frequencies of chosen BTLA gene polymorphisms (rs184489 and rs9288952) and the risk of Behcet disease. Materials and methods: The population of this study consisted of 108 patients with BD and 108 healthy controls. Genotyping for the rs184489 and rs9288952 polymorphisms were performed using PCR-RFLP method. Results: In terms of genotype and allele frequencies between the patient and control groups, there were no statistically significant differences (p > 0.05). However, there was a statistically significant difference in haplotype analysis between the two groups (p= 0.001). Moreover, carrying the T allele for the rs1844089 polymorphism and C allele for the rs9288952 polymorphism increase the risk of disease. Conclusion: Our findings propose that CT haplotype might have a potential function in the susceptibility to BD.
Elazi?'da Behçet hastaliklarinda BTLA gen polimorfizmlerinin araştirilmasi
Keywords: Behcet disease; BTLA; Polymorphism; SNP; PCR